Perhitungan Kelayakan Investasi Mesin Amplas Pada UD. Surya Sejati Dengan Pendekatan NPV Dan IIR - Muhammad Ferry Nasichul Achab; Hery Murnawan (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
Surya Sejati is a company engaged in manufacturing backrests, seats and table bases, in the production process of table mats there are problems of wasting time in the process of refining table mats, this study aims to analyze the activities of the production process and provide suggestions in the form of a sanding machine , and the results obtained are reduced production time, and work efficiency, the feasibility of the sanding machine will be tested by calculating the depreciation, machine costs, and production capacity time on the sanding machine, in calculating the feasibility of the sanding machine investment using the NPV (net present value) approach ) and IIR (internal rate of return) in order to determine whether the investment is feasible or not in business management at UD. Surya Sejati, in the calculation of investment feasibility the NPV value is more than 0, which is Rp.478,626,819. and the IIR (internal rate of return) value is 30% and the MAAR (Minimum Attractive Rate of Return) value is 12%, with a value (IIR > MAAR)